Pembinaan dan Pemberdayaan UMKM untuk Meningkatkan Pendapatan Masyarakat di Kelurahan Mandailing Kota Tebing Tinggi - Batubara, Rizki Wulanita; Purba, Rakhmawati; Siahaan, Rumiris; Mala, Nur; Akbar, Rafly Putra; Effendy, Yudi; Wibowo, Teguh (Community Service Progress, 2023)
The purpose of this service activity is to find out strategies for empowering MSMEs in increasing income, as well as the benefits for the community, namely receiving guidance and training from the Service Team in developing MSME businesses. The location of this service was carried out in Mandailing Village, Tebing Tinggi Kota District, targeting people who want to open Micro, Small and Medium Enterprises. Development of Micro, Small and Medium Enterprises is an effort by the central and regional governments. By coaching and empowering MSMEs in the midst of current free trade competition, it can provide encouragement to increase community income. This activity can encourage the economy of a region, not only increasing income but also equalizing income in a region. By providing community development and empowerment in Micro, Small and Medium Enterprises, job opportunities can be created for the Indonesian people, especially in Mandailing Subdistrict.